Exploring security in software architecture and design - Felderer, Michael; Scandariato, Riccardo (Information Science Reference, 2019)
"This book explores security in software architecture and design. It examines software security from a software engineering perspective and addresses technical, as well as managerial aspects of secure software engineering. It also includes all aspects of software security in the development, deployment, and management processes of software systems"--